2018
DOI: 10.1111/cas.13535
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of interleukin‐35 in intrahepatic cholangiocarcinoma is a prognostic indicator after curative resection

Abstract: Interleukin‐35 (IL‐35) is implicated in tumorigenesis, but its exact impact on intrahepatic cholangiocarcinoma (ICC) is not clear. The aim of the present study was to explore the specific effect of IL‐35 on patient prognosis. Additionally, we formulated an effective prognostic nomogram for ICC patients after curative resection. Immunohistochemistry was applied to explore IL‐35 expression as well as IL‐35 receptor (IL‐35R) in 102 ICC patients. Results showed that IL‐35 was highly expressed in ICC tumor tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…We found that overexpression of IL-35 in HCC was an independent risk factor for overall survival and recurrence. The GP130 and IL-12 Rβ2 receptors were also found to be expressed in HCC tissues, indicating a structural basis for the paracrine and autocrine function of IL-35, consistent with previous reports [22,30] . We further combined the expression levels of IL-35 and its receptors in HCC tissues, and found that patients with high expression of IL-35 and its receptors in tumor tissues had the worst prognosis, indicating that IL-35 expressed in HCC might activate the receptors of tumor cells through an autocrine pathway to promote the progression of liver cancer.…”
Section: Discussionsupporting
confidence: 91%
“…We found that overexpression of IL-35 in HCC was an independent risk factor for overall survival and recurrence. The GP130 and IL-12 Rβ2 receptors were also found to be expressed in HCC tissues, indicating a structural basis for the paracrine and autocrine function of IL-35, consistent with previous reports [22,30] . We further combined the expression levels of IL-35 and its receptors in HCC tissues, and found that patients with high expression of IL-35 and its receptors in tumor tissues had the worst prognosis, indicating that IL-35 expressed in HCC might activate the receptors of tumor cells through an autocrine pathway to promote the progression of liver cancer.…”
Section: Discussionsupporting
confidence: 91%
“…IL-35 played a pivotal role in the pathogenesis of tumor, progression, and prognosis. Tumor derived IL-35 has been demonstrated to promote tumor progression and to be a prognostic indicator in non-small cell lung cancer (20), intrahepatic cholangiocarcinoma (21), colorectal cancer (22, 23), prostate cancer (24), and breast cancer (25). However, controversy remained as to the expression profile of liver-resident and peripheral IL-35 expression in HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of significant correlation between IL-35 expression and prognosis in DLBCL patients contrasts with previous findings in other human tumors for which IL-35 expression in tumor was associated with a worse prognosis. However, whereas most studies identified IL-35 as a factor positively linked to tumor progression (10, 19, 20, 22, 24, 25), others suggested that IL-35 may play an anti-tumor role (21, 23). The impact of IL-35 in cancer most likely results from a combination of various factors involving expression of IL-35 receptor, tumor genomics, and specific features of tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…However, the high expression of IL-35 at sites of immune escape such as the fetal maternal interface (17) and in tolerogenic dendritic cells (18), favors a key role in immune tolerance. In addition, IL-35 expression by tumor cells or infiltrating lymphocytes has been reported in various types of human tumors including liver, pancreatic, colorectal, or breast cancer (10, 19–25). In most of these studies, IL-35 expression was associated with a worse prognosis (10, 19, 20, 22, 24, 25).…”
Section: Introductionmentioning
confidence: 99%